Volatility Spillovers in the Spanish Food Marketing Chain: The Case of Tomato. Issue 1 (9th April 2015) - Ait Sidhoum, Amer; Serra, Teresa
ABSTRACT: This research aims to assess volatility spillovers along the Spanish tomato marketing chain. A multivariate generalized autoregressive conditional heteroskedasticity (MGARCH) model is fit to weekly tomato prices at different levels of the marketing chain (producers, wholesalers and consumers). Empirical results suggest significant price transmission and volatility spillovers between different market levels. While causality links flow in all directions, volatility transmission is stronger from the consumer to the producer and wholesale prices rather than the other way around. Consumer price first and second moments are quite rigid, while producer and wholesale prices tend to suffer from higher instability.